Prevalence of Dental Fluorosis among 6-18-Year-Olds in Vidarbha, Maharashtra, and Its Association with Geological and Geochemical Fluoride Levels: A Cross-Sectional Study - Hajare, Shilpa T; Pusdekar, Yamini; Saoji, Ajeet V; Khatri, Sachin; Naitam, Ravi (National Journal of Community Medicine, 2025)
Background: Endemic Fluorosis is a longstanding public health problem caused by excess fluoride intake through drinking water or food products grown in soil with high fluoride content. Many areas in Maharashtra state, particularly the Vidarbha region are affected by fluorosis. The aim was to determine the prevalence of Dental Fluorosis in children of the age group of 6-18 years and corelate it with the fluoride levels in water, soil and foodgrains. Methods and Materials: A cross-sectional study will be conducted in randomly selected villages from Vidarbha region using multistage sampling. A total sample of 1230 children aged 6-18 years will be obtained. Dean`s index will be utilized for determining the prevalence of Dental Fluorosis. Fluoride levels of drinking water, soil and foodgrains will be analyzed. Results: The salient feature of the study is the fluoride levels in the drinking water and locally grown staple foodgrains like rice, jowar and wheat etc. This will generate evidence that corroborates with the fluorosis levels observed in the selected study region. Conclusion: The study will be a landmark in nearly a decade providing a comparative account of Dental Fluorosis in villages with high-to-moderate endemicity and co-relate clinical manifestations with fluoride levels in water, soil and foodgrains.